EXPLORATORY STUDY OF BEAUTY SERVICES AT GRIYA SEHAT RUMAH CANTIK ARTIK KLATEN - AS, Indarto; Kirwanto, AG; Setyawan, Intan Adista (Jurnal Jamu Kusuma, 2025)
A considerable number of individuals prefer traditional beauty services. Griya Sehat Rumah Cantik Artik is a traditional health service that provides beauty and wellness services. The objective of this study is to investigate the range of beauty services offered at Griya Sehat Rumah Cantik Artik. This study employs a qualitative research design, incorporating an exploratory approach and data collection methods such as in-depth interviews, observational studies, and document analysis. This exploratory research focuses on service description, but it does not measure the extent to which the service is truly effective in achieving its goals (improving skin beauty/health) or how it compares to modern methods. The study’s results indicate that the beauty services offered at Griya Sehat Rumah Cantik Artik include beauty cupping, facials, beauty acupuncture, facial acupressure, and body scrubs. The array of skills used to provide beauty services includes beauty cupping, facial massage, facials, beauty acupuncture, and body scrubs. These services entail meticulous preparation of tools, materials, patients, and therapists, as well as delineating the stages involved in delivering beauty services. Griya Sehat Rumah Cantik Artik offers beauty services designed to help the community, particularly women, enhance their aesthetic appeal and maintain optimal skin health.